New method for benchmarking traffic safety level for the territory - Pešić, Dalibor; Vujanić, Milan; Lipovac, Krsto; Antić, Boris (Transport, 2013)
Evaluation, monitoring and comparison of traffic safety in various territories presents a major challenge to the traffic safety researches. Recently a large number of studies are focused on finding an appropriate method for the calculation of the traffic safety level which uses a single numerical value for its assessment. For that purpose, traffic safety indicators are combined into a single numerical value by appropriate techniques in order to represent a grade of the traffic safety level. This paper contains, after the summary of contemporary tendencies in the evaluation of traffic safety levels, the analysis of methods used in the evaluation of traffic safety levels so far in Serbia with the emphasis on their values and deficiencies. Considering those analyses, this paper introduces a new method for traffic safety level evaluation the so called Benchmarked Traffic Safety Level (BTSL). BTSL implies selection of appropriate indicators, transformation of chosen indicators, assigning weights and aggregation. The proposed scale appliance enables traffic safety level to define for the territory, and also compares it with a similar one. BTSL provides a single numerical value so that to evaluate the traffic safety level for the territory, derived from the aggregation of previously transformed and ‘weighted’ three outcomes indicators and three safety performance indicators.First Published Online: 03 Apr 2013